A biomechanical report of an acute lateral ankle sprain during a handball-specific cutting movement - Bagehorn, T.; Bill, K.; Mai, P.; Krosshaug, T.; Kersting, U. G. (Sports Biomechanics, 2024)
Biomechanical measurements of accidental ankle sprain injuries are rare but make important contributions to a more detailed understanding of the injury mechanism. In this case study, we present the kinematics and kinetics of a lateral ankle sprain of a female athlete performing handball-specific fake-and-cut manoeuvres. Three-dimensional kinematics and kinetics were recorded and six previously performed trials were used as reference. Plantarflexion, inversion, and internal rotation angles were substantially larger than the reference trials and peaked between 190 and 200 ms after initial ground contact. We observed a highly increased inversion and internal rotation moment. However, compared to the non-injury trials the data also revealed a reduction in the second dorsiflexion moment peak. Ground reaction forces were lower throughout the injury trial. Other parameters at initial ground contact including ankle and hip position, step length, and the traction coefficient indicate that a preparatory maladjustment occurred. This study adds valuable contributions to the understanding of lateral ankle sprains by building upon previously published reports and considering the shoe-surface interaction as an important factor for injury.